Rhizosphere bacterial communities of three minor grain crops exhibit distinct environmental adaptations and assembly processes - Tian, Lixin; Zhang, Feifei; Chen, Pengliang; Zhang, Panpan; Gao, Zhijun; Dong, Yang; Yan, Feng; Yang, Pu; Gao, Xiaoli; Feng, Baili (European journal of soil science, 2022)
Deciphering responses of bacterial communities to environmental change, and understanding how communities assemble in response to environmental change, are important subjects. The assembly processes governing the rhizosphere bacterial communities of minor grain crops are rarely explored based on regional scales, especially in terms of the environmental adaptation. Here, we investigated the environmental thresholds and phylogenetic signals for ecological preferences of rhizosphere bacterial communities of three minor grain crop taxa across complex environmental gradients to reflect their environmental adaptation. Additionally, we reported environmental factors affecting their community assembly processes based on a large‐scale soil survey in agricultural fields across northern China using high‐throughput sequencing. The results demonstrated a narrower range of environmental thresholds and weaker phylogenetic signals for the ecological traits of rhizosphere bacteria in proso millet than in foxtail millet and sorghum fields. The proso millet rhizosphere community was the most phylogenetically clustered. Null model analysis indicated that homogeneous selection belonging to deterministic processes governed the sorghum rhizosphere community, whereas dispersal limitation belonging to stochastic processes was the critical assembly process in the foxtail millet and proso millet. Mean annual temperature was the decisive factor for adjusting the balance between stochasticity and determinism of the foxtail millet, proso millet and sorghum rhizosphere communities. A higher temperature resulted in stochasticity in the proso millet and sorghum communities. For the foxtail millet community, the deterministic assembly increased with an increase in temperature. These results contribute to the understanding of rhizosphere‐associated bacterial community assembly processes in agro‐ecosystems on a large scale. Highlights Proso millet rhizosphere bacterial taxa exhibited weaker environmental adaptation than foxtail millet and sorghum taxa. Determinism governed the sorghum rhizosphere community, whereas stochasticity was the critical assembly process in the foxtail and proso millet. Mean annual temperature mediated balance between stochastic and deterministic processes.